Gyo Fujikawa's Oh, what a busy day!. - Fujikawa, Gyo. (New York : Grosset & Dunlap, 1976)
Pictures and brief text illustrate the myriad activities which fill the days of young children.
School Library Journal
3.4
K-3
Keywords: Children's poetry; Children's poetry